Comparative Analysis of the Degree of Acidity of Rainfall in the City of Cusco and its Diagnosis in 2017 - Tello-Yarina, Jonny; Seguraa, Salinova Carrillo; La Torre, Mayra Irina Garcia; Yarin, Eddy Tello; Gamarra, Maribel Palomino; Huallpa, Juvenal Pérez; Ballón, Venancia Ccollatupa; Atauchi, Rubén Ingles (Journal of Posthumanism, 2025)
As in the latter city of Cusco, second-hand and new vehicles have been significantly increased, but without any specification and control of environmental issues, such as vehicle emissions filters, resulting in atmospheric pollution that has increased in form Alarming the emission of gases that go to the atmosphere and when rainfall occurs, these are producing chemical reactions with SOx and NOx, which fall and increase the acidity of rainwater, if the acidity is the same Or less than pH 5.6- Arauzo, G. (2007) is considered acid rain. The general objective of this study is to perform the comparative analysis of the degree of acidity of rainfall in the city of Cusco and its diagnosis in 2017 and as specific objectives: Identify the district with the highest acidity of rainfall; Identify the months with the highest degree of rain acidity; establish the confidence limits of acidity of rainfall in the city of Cusco and compare with the permissible limit.The present study has as general objective to determine the degree of acidity of rainfall in the city of Cusco in 2015 and 2016, and as specific objectives the measurement of the pH of rainwater in the months of rainy season and the Comparing the acid rain pH of the literature with data obtained from the pH of rainfall in the city of Cusco. It is concluded that in the city of Cusco there is no acid rain since the average acidity is 5, 728 pH, but in the months of November and December there is the presence of acid rain with average values of 5,317 and 5,16 pH respectively.